2015
DOI: 10.1002/ajmg.a.37085
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of a next generation sequencing panel assay for Marfan and Marfan‐like syndromes featuring aortopathy

Abstract: Aortopathy can be defined as aortic dilation, aneurysm, dissection, and tortuosity. Familial aortopathy may occur secondary to fibrillin-1 (FBN1) mutations in the setting of Marfan syndrome, or may occur as a result of other genetic defects with different, but occasionally overlapping, phenotypes. Because of the phenotypic overlap and genetic heterogeneity of disorders featuring aortopathy, we developed a next generation sequencing (NGS) assay and comparative genomic hybridization (CGH) array to detect mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 36 publications
6
51
1
Order By: Relevance
“…In this cohort of 810 patients, a pathogenic or likely pathogenic variant was identified in 66 patients (8.1%). Overall, we identified a relatively low number of pathogenic or likely pathogenic variants in our H-TAD cohort compared to pre-vious studies that identified mutations in 10.3% to 35.5% (Campens et al, 2015;Lerner-Ellis et al, 2014;Poninska et al, 2016;Proost et al, 2015;Wooderchak-Donahue et al, 2015;Ziganshin et al, 2015). This wide range is likely to be explained by differences in clinical and demographic characteristics of the study populations and different inclusion criteria used for genetic testing.…”
Section: Discussionmentioning
confidence: 78%
“…In this cohort of 810 patients, a pathogenic or likely pathogenic variant was identified in 66 patients (8.1%). Overall, we identified a relatively low number of pathogenic or likely pathogenic variants in our H-TAD cohort compared to pre-vious studies that identified mutations in 10.3% to 35.5% (Campens et al, 2015;Lerner-Ellis et al, 2014;Poninska et al, 2016;Proost et al, 2015;Wooderchak-Donahue et al, 2015;Ziganshin et al, 2015). This wide range is likely to be explained by differences in clinical and demographic characteristics of the study populations and different inclusion criteria used for genetic testing.…”
Section: Discussionmentioning
confidence: 78%
“…Increasingly extensive gene panels, as well as whole exome and genome sequencing, are used to interrogate the growing number of genes implicated in Mendelian diseases1. However, such panels only modestly increase the number of high-confidence diagnostic results while identifying ever larger numbers of variants of uncertain significance (VUS)2,3; these inconclusive results not only reduce the clinical utility of testing but can lead to mis-interpretation and mis-diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly extensive gene panels are used to interrogate the growing number of genes implicated in Mendelian diseases (1). However, such panels only modestly increase the number of high-confidence diagnostic results while identifying ever larger numbers of variants of uncertain significance (VUS) (2)(3)(4). The likelihood that a rare variant is indeed pathogenic depends on the pre-test probability that the patient has the relevant disease.…”
Section: [Main Text: ] Introductionmentioning
confidence: 99%